2020
DOI: 10.3389/fmicb.2020.01088
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of the CRISPR-Cas System and Prophages Present in the Genome Reveals the Co-evolution of Bifidobacterium pseudocatenulatum and Phages

Abstract: Diverse CRISPR-Cas systems constitute an indispensable part of the bacterial adaptive immune system against viral infections. However, to escape from this immune system, bacteriophages have also evolved corresponding anti-defense measures. We investigated the diversity of CRISPR-Cas systems and the presence of prophages in the genomes of 66 Bifidobacterium pseudocatenulatum strains. Our findings revealed a high occurrence of complete CRISPR-Cas systems (62%, 41/66) in the B. pseudocatenulatum genomes. Subtypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
3
11
0
Order By: Relevance
“…Genome sequencing and comparative genomics of seven newly sequenced and 50 publicly available E. lenta isolates allowed us to establish that 5.6% of the orthologous groups (OGs) that form the pangenome of E. lenta can be associated with prophages. This value is within range for prophages infecting other species of Actinobacteria, estimated at between 2% to 6.7% of OGs forming the Bifidobacterium pangenome [77,93].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Genome sequencing and comparative genomics of seven newly sequenced and 50 publicly available E. lenta isolates allowed us to establish that 5.6% of the orthologous groups (OGs) that form the pangenome of E. lenta can be associated with prophages. This value is within range for prophages infecting other species of Actinobacteria, estimated at between 2% to 6.7% of OGs forming the Bifidobacterium pangenome [77,93].…”
Section: Discussionsupporting
confidence: 61%
“…These observations may explain the lack of an obvious correlation between the presence or absence of a CRISPR/cas system and the number of prophages associated with a host genome. As has been determined for other Actinobacteria genera such as Bifidobacterium, the presence of CRISPR/cas does not mean a bacterium genome will possess fewer prophage elements in its genome [93].…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the pores near the surface are more effectively sealed by MICP than the deeper pores in the brick cubes as revealed by X-ray micro-CT. Chen et al [33] and Sun et al [34] also demonstrated that the internal concrete cracks could not be repaired as well as the cracks near the surface. One possible reason could be that the fluidity of the MICP medium is relatively low likely due to the silica powder mixed into the slurry [10]. MICP with pure liquid media can directly repair cracks with a width less than 0.4 mm, while for wider cracks, it is necessary to use fine sand, silica powder, and/or other fillers [35].…”
Section: Micp Improved the Water-resistance Property Of Bricksmentioning
confidence: 99%
“…They can adsorb Ca 2+ from the solution as crystallization nuclei, producing microbial-induced calcite bridges on the adjacent particles to form cemented bio-calcareous rock [8]. Inspired by the natural ability of MICP, researchers have used this technique as a promising self-healing technology for concrete crack remediation and improvement of ash bricks [9,10]. Therefore, MICP could also be a biological control tool against the cracks of city wall bricks as well as for other ancient remnants subjected to deterioration from uncontrolled cracking.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, bacterial numbers are estimated at 10 11 cells per gram weight of fecal material compared to approximately 10 12 bacteriophages in the same amount ( Cani, 2018 ). Bacteriophages have been shown to drive the composition of the gut microbiome ( Moreno-Gallego et al, 2019 ) by specifically targeting gut bacteria and creating an evolutionary arms race between bacterial host and virus ( Azam and Tanji, 2019 ; Wang G. et al, 2020 ). Further, studies have shown the capacity of bacteriophages to disrupt biofilms ( Hansen et al, 2019 ; Lusiak-Szelachowska et al, 2020 ), kill intracellular bacteria ( Jonczyk-Matysiak et al, 2015 ), and modulate the immune system ( Van Belleghem et al, 2018 ), all key to counteracting virulence mechanisms that oncobacteria use to promote tumor growth ( Holt and Cochrane, 2017 ).…”
Section: Introductionmentioning
confidence: 99%